Efektivitas Kartu Kesuma dengan Metode Game Based Learning terhadap Materi Perilaku Hidup Bersih dan Sehat Siswa SDN Sumber Kokap 1 Kabupaten Bondowoso - Muhammad Wahyu Hidayat; Leny Agustin Indah Sari; Bella Pratiwi; Talitha Eudora Nadhif Widyadhana; Nurdiana Holidah; Farazel Alya Nurfadila; Agung Nugroho Puspito; Isvina Unaizahroya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The low level of awareness among primary school pupils regarding Clean and Healthy Living Behaviours (PHBS) is the main issue underlying this community service initiative, particularly at SDN Sumber Kokap 1 in Bondowoso Regency. The aim of the initiative is to enhance the knowledge and awareness of pupils in Years 4 to 6 regarding the importance of practising PHBS in their daily lives through an engaging and interactive approach. The activity was conducted over five sessions using the Game-Based Learning (GBL) method, supported by an innovative learning tool known as the Kesuma Cards (Health for the Future). The learning sessions included a pre-test, the delivery of basic PHBS material, a handwashing demonstration, reinforcement of the material through the Kesuma Card game, and a post-test as a final evaluation. A total of 34 pupils actively participated in the entire series of activities. The results of the activities showed a significant improvement in the pupils’ understanding, as demonstrated by an increase in the average pre-test score from 37.73 to 84.91 in the post-test. Furthermore, the pupils displayed high levels of enthusiasm and active engagement throughout the learning process. The use of Kesuma Cards in this activity proved effective in improving students’ understanding of PHBS, developing critical thinking skills, strengthening cooperation, and fostering positive character traits from an early age. This activity made a tangible contribution to building healthy lifestyle habits among primary school pupils in the Taman Krocok sub-district, Bondowoso Regency.